Perancangan Sistem Inventarisasi Aset Terpadu Berbasis Web di Lingkungan Perguruan Tinggi - Fakihah Farhah Faridaashri; Mahendra Dewantoro; Damayanti Damayanti (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Asset management in higher education institutions is essential to ensure efficiency, transparency, and accountability in the use of resources. However, many institutions still rely on manual or semi-digital systems, leading to data duplication, information inconsistency, and difficulties in reporting. This study aims to develop an Integrated Web-Based Asset Inventory System to address these issues. The research methodology follows a Research and Development (R&D) approach, combining Prototype and Waterfall methods. The system is designed through stages including needs analysis, UML design, implementation using technologies such as PHP/CodeIgniter, MySQL, and Bootstrap, followed by functional and usability testing. Key features of the system include asset data input and updating, categorization by type and location, periodic notifications, automated reporting, role-based access control, and activity logs. The results show that the system provides an accurate, real-time, and integrated solution for asset management. With the appropriate use of information technology, this system is expected to improve operational efficiency and serve as a reference for other educational institutions in implementing digital-based asset management.